Dipstick urine analysis screening among asymptomatic dogs of k9 units: Marai Hamid Saad Mohmoud1 and Ali Hussein Al-Dujaily2 - Mohmoud, Marai Hamid Saad (The Iraqi Journal of Veterinary Medicine, 2018)
The study was designed to determine the abnormal urine components such as red blood corpuscles, protein, bilirubin, nitrites, specific gravity, glucose, hydrogen ion, ketones, urobilinogen and leukocyte abnormality in k9 dogs urine.The present study was carried out on 135 asymptomatic dogs (65 males and 70 females) with age (2 – 8 years) in Al-Najaf governorate between February 2016 and April 2016. At morning, urine specimens were collected from dogs and tested via method of dipstick. Mass urinary screening is a suitable tool to detect dogs with asymptomatic progressive renal diseases, however the urinalysis can deliver to us information not merely about the kidneys and bladder, but also the liver, pancreas, and other organs, as well as, helping to make a diagnosis, in addition to determining a prognosis (a prediction of the consequence of the disease) and response to treatment. Results showed that 46 (34%) dogs were with urinary abnormalities, hematuria was the most frequent abnormality showed 28(60.9%), nitrituria 10(21.7%), proteinuria 4(8.7%), bilirubinuria in 2(4.3%) and decreased specific gravity 2(4.3%) respectively, pH (0%), glucose (0%), ketones (0%), urobilinogen (0%) and leukocyte (0%).